Nanosecond pulse generators with inductive storage; Proceedings of the 1st IEEE International Pulsed Power Conference, Lubbock, Texas, november 9-11, 1976 - Kotov Yu. A.; Kolganov N. G.; Kovaltchuk B. M.; Mesyats G. A. Gennady Andreyevich; Sedoi V. S. (1976, 1976)
В фонде НТБ ТПУ отсутствует